Molecular dynamics simulations of retinal in rhodopsin: from the dark-adapted state towards lumirhodopsin. - Lemaître, V; Yeagle, P; Watts, A (2005)
The formation of photointermediates and conformational changes observed in the retinal chromophore of bilayer-embedded rhodopsin during the early steps of the protein activation have been studied by molecular dynamics (MD) simulation. In particular, the lysine-bound retinal has been examined, focusing on its conformation in the dark-adapted state (10 ns) and on the early steps after the isomerization of the 11-cis bond to trans (up to 10 ns). The parametrization for the chromophore is based on a recent quantum study [Sugihara, M., Buss, V., Entel, P., Elstner, M., and Frauenheim, T. (2002) Biochemistry 41, 15259-15266] and shows good conformational agreement with recent experimental results. The isomerization, induced by switching the function governing the dihedral angle for the C11=C12 bond, was repeated with several different starting conformations. From the repeated simulations, it is shown that the retinal model exhibits a conserved activation pattern. The conformational changes are sequential and propagate outward from the C11=C12 bond, starting with isomerization of the C11=C12 bond, then a rotation of methyl group C20, and followed by increased fluctuations at the beta-ionone ring. The dynamics of these changes suggest that they are linked with photointermediates observed by spectroscopy. The exact moment when these events occur after the isomerization is modulated by the starting conformation, suggesting that retinal isomerizes through multiple pathways that are slightly different. The amplitudes of the structural fluctuations observed for the protein in the dark-adapted state and after isomerization of the retinal are similar, suggesting a subtle mechanism for the transmission of information from the chromophore to the protein.